Phosphoramidate pronucleotides of cytostatic 6-aryl-7-deazapurine ribonucleosides - Perlíková, Pavla; Pohl, Radek; Votruba, Ivan; Shih, Robert; Birkuš, Gabriel; Cihlář, Tomáš; Hocek, Michal (Bioorganic & medicinal chemistry, 2011)
A series of O-phenyl methyl-, ethyl- and benzylalanyl phosphoramidate pronucleotides derived from cytostatic 6-aryl-7-deazapurine ribonucleosides were prepared by the cross-coupling reactions of the 2',3'-isopropylidene protected 6-chloro-7-deazapurine ribonucleoside phosphoramidates with (het)arylboronic acids or -stannanes followed by deprotection. Most of the prepared prodrugs exerted in vitro cytostatic effects against both solid tumor and lymphoid cancer cells within low micromolar range of concentrations. These activities were in general weaker or comparable to the activities of the parent nucleosides. Additional testing of selected prodrugs suggests that the lack of activity improvement over parent nucleosides is not due to the lack of permeability or inefficient catabolism of alanyl-ester by intracellular hydrolases. More likely, active efflux of prodrugs may play a role in their weak cytotoxic activity.
Keywords: purinové nukleosidy; nádorové buněčné linie; protinádorové látky; hmotnostní spektrometrie s elektrosprejovou ionizací; Purine Nucleosides; Antineoplastic Agents; Spectrometry, Mass, Electrospray Ionization; Cell Line, Tumor; Humans; Magnetic Resonance Spectroscopy; lidé; magnetická rezonanční spektroskopie